Desain Lintasan Belajar Kubus dan Balok dengan Pendekatan Pendidikan Matematika Realistik Indonesia di Kelas V Sekolah Dasar - Witri Rahmayani; Zetra Hainul Putra; Eddy Noviana (Universitas Islam Sultan Agung, 2021)
This study aims to design a learning trajectory of cubes and rectangular prisms with a realistic Indonesian mathematics education approach. This study uses design research as a method to achieve the objectives of this study. Design research consists of 3 stages: the preliminary stage, the experiment stage, and the retrospective analysis stage. To check the validity of the data used, the researchers used triangulation techniques, especially source triangulation. To explore the validity of the information, the researchers used several data sources, namely interviews with several students, observations from videos during learning, and observations of student worksheets. The designed learning trajectory was tested two times, namely a pilot study with four students and a teaching experiment with eight students from fifth graders. The results showed that the design of the cube and rectangular prisms learning trajectory with an Indonesian realistic mathematics education approach facilitated students' understanding of the concept of cubes and rectangular prisms..